Ultrafast stiffening of concentrated thermoresponsive mineral suspensions. (September 2022) - Bhagavathi Kandy, Sharu; Mehdipour, Iman; Neithalath, Narayanan; Kumar, Aditya; Bauchy, Mathieu; Garboczi, Edward; Srivastava, Samanvaya; Gaedt, Torben; Sant, Gaurav
Graphical abstract: Highlights: A facile pathway to achieve controllable, rapid stiffening in aqueous suspensions that are compatible with extrusion-based 3D printing. Thermoresponsive-concentrated mineral suspensions are formulated using thermally triggered epoxy-thiol condensation-polymerization reactions. Thermal latency, tunable induction period, and rapid stiffening are realized in concentrated mineral suspensions. Suspensions exhibit rapid solidification in timescales of seconds to minutes upon bulk thermal activation, achieving average stiffening rates up to 400 Pa/s. Offer new pathways to overcome the limitations of traditional suspension-based printing and expand the design and production space accessible for architected structural components. Abstract: Extrusion-based 3D printing with rapidly hardening polymeric materials is capable of building almost any conceivable structure. However, concrete, one of the most widely used materials for large-scale structural components, is generally based on inorganic binder materials like Portland cement. Unlike polymeric materials, a lack of precise control of the extent and rate of solidification of cement-based suspensions is a major issue that affects the ability to 3D-print geometrically complex structures. Here, we demonstrate a novel method for controllable-rapid solidification of concentrated mineral suspensions that contain a polymer binder system based on epoxy and thiol precursors as well as one or more mineral fillers like quartz and calcite. The thermally triggered epoxy-thiol condensation polymerization induces rapid stiffening of the hybrid suspensions (0.30 ≤ ϕ ≤ 0.60), at trigger temperatures ranging between 50 °C and 90 °C achieving average stiffening rates up to 400 Pa/s. The use of nucleophilic initiators such as 1-methylimidazole provides control over the activation temperature and curing rate, thereby helping to achieve an adjustable induction period and excellent thermal latency. By using multiple techniques, we provide guidelines to create designer compositions of mineral suspensions that utilize thermal triggers to achieve thermal latency and ultrafast stiffening – prerequisite attributes for 3D-manufacturing of topologically-optimized structural components.